2015
DOI: 10.2174/1567202612666150603140912
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Treatments with Quetiapine Increase Mitochondrial Respiratory Chain Complex Activity in the Rat Brain

Abstract: Several studies have found that the molecular mechanisms of mitochondrial energy metabolism are impaired in major depressive disorder (MDD). Classic antidepressants and atypical antipsychotics can alter the function of enzymes involved in adenosine triphosphate (ATP) metabolism. Quetiapine is an atypical antipsychotic that, in addition to having a therapeutic benefit in treating MDD, appears to exert antioxidant and neuroprotective effects. Therefore, we aimed to evaluate the acute and chronic effects of queti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In animal studies, treatment with intraperitoneal injections of olanzapine for 28 days had effects on amygdalar and hippocampal neuronal populations which were thought to be caused by a change in neuropeptide activity in rats (Palasz et al, 2016). Acute one hour and chronic 14 days treatment with quetiapine increased the mitochondrial respiratory chain complex activity in the rat hippocampus, amygdala, and nucleus accumbens (Ignacio et al, 2015). To our knowledge, it has not been reported whether these changes were related to increased subcortical volumes in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, treatment with intraperitoneal injections of olanzapine for 28 days had effects on amygdalar and hippocampal neuronal populations which were thought to be caused by a change in neuropeptide activity in rats (Palasz et al, 2016). Acute one hour and chronic 14 days treatment with quetiapine increased the mitochondrial respiratory chain complex activity in the rat hippocampus, amygdala, and nucleus accumbens (Ignacio et al, 2015). To our knowledge, it has not been reported whether these changes were related to increased subcortical volumes in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 52 ] Some studies had reported that atypical antipsychotics and antidepressants may alter CK concentration and activity in the plasma and brain. [ 53 55 ] After the antidepressant treatment with paroxetine, CK activity was increased in the prefrontal cortex, hippocampus, and striatum of rats, and CK levels were increased in the serum of a patient with depression. Thus, the increase in CK activity elevated by paroxetine may be related to increased concentrations of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Animals received daily intraperitoneal injections of quetiapine (20 mg/kg) for 14 days. The concentration and treatment period considered a first study published by Ignácio et al [26] that used quetiapine at the doses of 20, 40 and 80 mg/kg. Lower concentrations of quetiapine elevated the activity of mitochondrial respiratory chain complexes [26].…”
Section: Drugs and Experimental Designmentioning
confidence: 99%
“…The concentration and treatment period considered a first study published by Ignácio et al [26] that used quetiapine at the doses of 20, 40 and 80 mg/kg. Lower concentrations of quetiapine elevated the activity of mitochondrial respiratory chain complexes [26]. Furthermore, an unpublished pilot study from our group showed that the concentration of quetiapine at the dose of 80 mg/kg administered acutely revealed a sedative effect, while the concentrations of 20 and 40 mg/kg did not promote sedation, compared to control animals treated with saline.…”
Section: Drugs and Experimental Designmentioning
confidence: 99%